Pengembangan Teknologi Kapal Tanpa Awak Guna Mendukung Operasi dan Latihan TNI Angkatan Laut - Hendri Priyono; Sovian Aritong; Mahesa Akbar (CV. Publikasi Indonesia, 2022)
Ship resistance is an important factor in ship design. Technological developments are carried out to reduce the magnitude of the ship's resistance. By reducing the drag of the ship, it can improve the performance of the ship with the same engine power as the previous design. In this study, we will redesign the hull of the Indonesian Navy's unmanned vessel in order to increase the performance of the ship's speed. The process of redesigning the hull of this unmanned ship uses the numerical method using Maxsurf software in analyzing hydrodynamic performance. The results of the drag analysis carried out with a redesign show a decrease in the value of the ship's resistance by 1143 KN and the required power of 9.98 HP. From the results that this study obtained compared to the initial design of 60%.